A Catalytically Inactive Lys49 PLA2 Isoform from Bothrops jararacussu venom that Stimulates Insulin Secretion in Pancreatic Beta Cells - Fagundes, Fabio H. R. [UNESP]; Aparicio, Ricardo; dos Santos, Marcelo L.; Diz Filho, Eduardo B. S. [UNESP]; Oliveira, Simone C. B. [UNESP]; Toyama, Daniela O.; Toyama, Marcos H. [UNESP] (Bentham Science Publ Ltd, 2011)
A new secretory phospholipase A2 (sPLA2) isoform from Bothrops jararacussu venom (BjVIII) has been characterized by causing platelet aggregation, an absent activity in BthTx-I, Prtx-I and PrTx-II sPLA2s. According to our results, BjVIII also enhances insulin release by the pancreatic beta cells. The complete amino acid sequence of the new isoform was determined by Edman degradation and de novo peptide sequencing. These analyses showed a G35K amino acid modification for BjVIII in comparison with BthTx-I, PrTx-I and Prtx-II, a structural difference that has been related to the conflicting biological activities among BjVIII and other Lys49 sPLA2s. The whole set of evidences collected in this work indicates that, besides the C-terminal region and B-wing of PLA2, the calcium binding loop in BjVIII should be considered as an important region, involved in the pharmacological effects of Lys49-sPLA2 isoforms from the Bothrops genus.
Keywords: Bothrops jararacussu; edman degradation; insulin secretion; mass spectra; pancreatic beta cells; PLA2; platelet aggregation